2013
DOI: 10.1038/nature12517
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral organoids model human brain development and microcephaly

Abstract: The complexity of the human brain has made it difficult to study many brain disorders in model organisms, and highlights the need for an in vitro model of human brain development. We have developed a human pluripotent stem cell-derived 3D organoid culture system, termed cerebral organoid, which develops various discrete though interdependent brain regions. These include cerebral cortex containing progenitor populations that organize and produce mature cortical neuron subtypes. Furthermore, cerebral organoids r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

100
4,679
1
24

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 4,159 publications
(5,059 citation statements)
references
References 56 publications
(63 reference statements)
100
4,679
1
24
Order By: Relevance
“…Previously it was shown that high‐density NSC cultures spontaneously form neural aggregates that recapitulate several NSC niche components 37. In line with this, large neural aggregates or neural organoids exhibiting CNS tissue architecture have recently been described 38, 39. It has also been proposed that MICs could offer further benefits for culturing NSCs and NSC‐derived cells.…”
Section: Introductionmentioning
confidence: 84%
“…Previously it was shown that high‐density NSC cultures spontaneously form neural aggregates that recapitulate several NSC niche components 37. In line with this, large neural aggregates or neural organoids exhibiting CNS tissue architecture have recently been described 38, 39. It has also been proposed that MICs could offer further benefits for culturing NSCs and NSC‐derived cells.…”
Section: Introductionmentioning
confidence: 84%
“…Building on these earlier works, a recent flurry of papers described the generation of various neural organoids (Table 1), ranging from the whole‐brain organoids,27, 28, 29 to large sub‐brain regions such as cortical organoids,30, 31 to specific regions, including cerebellum,32 midbrain,33 adenohypophysis,34 hypothalamus,35 and hippocampus 36. Comparing with the classical neurospheres, these organoids are generally much larger.…”
Section: Brain Organoids: Current Technologiesmentioning
confidence: 99%
“…In addition to the increased size, cerebral organoids showed highly thickened neuronal lobes within which neural progenitors and neurons reside. Immunostaining analysis revealed the presence of distinct zones such as the ventricular zone (VZ), the intermediate zone (IZ), and even the cortical plate‐like structure, similar to the developing brain 27, 29. Particularly exciting is the presence of so‐called outer subventricular zone (oSVZ), an embryonic structure that is uniquely expanded in humans but absent in rodents.…”
Section: Brain Organoids: Current Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent development of stem cell–based tissue engineering technology has provided a promising strategy for treating SCI 4. With the insights gained from developmental biology and the advancement in 3D culturing, tissue engineering has entered a new era of constructing of multiple tissue types or organoids 5. It is believed that tissue engineering would help realize constructing a functional tissue or organoid through the combination of stem cells, functional biomaterials, and neurotrophic factors to treat diseases of the central nervous system, including SCI 6…”
Section: Introductionmentioning
confidence: 99%